2019
DOI: 10.1002/ejhf.1407
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic implications of plasma volume status estimates in heart failure with preserved ejection fraction: insights from TOPCAT

Abstract: Aims Plasma volume expansion is clinically and prognostically relevant in individuals with heart failure. Prior cohorts either excluded or had limited representation of patients with heart failure with preserved ejection fraction (HFpEF). We aimed to examine the relationship between calculated plasma volume status (PVS) and outcomes in HFpEF. Methods and results We included enrollees from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist Trial (TOPCAT) with available haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…The characterization and recruitment of HF patients was in concordance with the guidelines set in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist clinical trial (24), which was prior to the setting of the new European Society for Cardiology guidelines (1). Therefore, HF patients recruited from the MHI Heart Failure Clinic were classified as HFrEF if their LVEF was #40% or HFpEF if their LVEF was $45% (24)(25)(26), as documented by contrast ventriculography, magnetic resonance imaging, radionuclide ventriculography, or quantitative echocardiography within the previous 12 mo if no cardiac event occurred since the measurement of their LVEF (24). In addition to the previous inclusion criteria for the HF patients, the HF plus T2DM patients had also an HbA1c ,10% and were controlled by any available hypoglycemic medications and, as per guidelines, were treated with preventive hypertension medication.…”
Section: Selection Criteria Of Healthy Volunteers and Patientsmentioning
confidence: 99%
“…The characterization and recruitment of HF patients was in concordance with the guidelines set in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist clinical trial (24), which was prior to the setting of the new European Society for Cardiology guidelines (1). Therefore, HF patients recruited from the MHI Heart Failure Clinic were classified as HFrEF if their LVEF was #40% or HFpEF if their LVEF was $45% (24)(25)(26), as documented by contrast ventriculography, magnetic resonance imaging, radionuclide ventriculography, or quantitative echocardiography within the previous 12 mo if no cardiac event occurred since the measurement of their LVEF (24). In addition to the previous inclusion criteria for the HF patients, the HF plus T2DM patients had also an HbA1c ,10% and were controlled by any available hypoglycemic medications and, as per guidelines, were treated with preventive hypertension medication.…”
Section: Selection Criteria Of Healthy Volunteers and Patientsmentioning
confidence: 99%
“…Peter et al reported that PVS of -6.5% optimally predicted absence of adverse outcomes, and the rate of cardiac events were increased with advancing plasma expansion in patients with heart failure with reduced ejection fraction and those with mid-range ejection fraction [18]. The TOPCAT study demonstrated that increment in PVS is associated with a higher risk of all-cause death and heart failure hospitalization in patients with heart failure with preserved ejection fraction [13]. Taking these results into consideration, PVS could be a useful predictor of poor clinical outcome in patients with heart failure independently of ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plasma volume status (PVS), an index of the degree to which patients have deviated from their ideal plasma volume, is gaining attention in patients with heart failure. PVS is associated with cardiac events and mortality in patients with heart failure [ 13 15 ]. American College of Cardiology/American Herat Association guidelines have recommended volume status be assessed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…between spironolactone use and calculated plasma volume for any endpoint. 10,11 In this issue of the journal, Kalogeropoulos et al 12 provide important further insights into the effects of spironolactone on subsequent diuretic use, electrolytes and serum creatinine, as well as their relationship with the risk for HF readmission. In brief, spironolactone had a marginal (<1%) and short-term (first 8 months) effect on weight loss in the American population of the TOPCAT trial, with superimposed curves after 1 year.…”
mentioning
confidence: 99%